A predictive mechanism to measure the academic achievement of high school students in general emergency circumstances – Coronavirus "COVID-19" as a model – - Asiri, Ibrahim Abdullah; Alsubaihi, Ali Ahmed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to propose a prediction-based mechanism for measuring the academic achievement of high school students in general emergency conditions, "the Corona pandemic as a model". In order to achieve the objective of the study, the researcher adopted the predictive approach, and the researcher relied on withdrawing data from the Noor system and then processing it statistically. The study sample consisted of the results of (164) students. The results of the study showed a statistically significant correlation between the students’ grades in the course (Math 6) with the mean (m) of the students’ scores in the (Math 1 - Math 5) courses, the statistical significance of predicting the (Math 6) course using the average (m) of the students’ scores in the (Math 5) courses. Within the limits of the study sample used, it is significant compared to the students’ grades with the knowledge of all courses (Math 1 - Math 5) in the multiple regression model, that it is possible to predict the academic achievement of students with a course (Math 6) which is predicted by knowing the average (m) of the scores observed in the Noor system for students In their previous courses (Math 1 - Math 5). In light of the results, the study recommended giving educational decision-makers a proposed scientific solution to measure students’ academic achievement in general emergency conditions “the Corona pandemic as a model” or even for an individual student. The study ended with proposals, the most important of which is conducting similar studies in predicting the measurement of academic achievement in other courses, other educational departments, and a larger sample size.
Keywords: Prediction; Measurement; Academic achievement; High School Students; Emergency Conditions; Corona Pandemic “Covid-19